2008
DOI: 10.1243/03093247jsa349
|View full text |Cite
|
Sign up to set email alerts
|

T-stress determination using thermoelastic stress analysis

Abstract: T-stress and mixed-mode stress intensity factors have been determined experimentally using thermoelastic stress analysis and using a finite element method. Pure mode I, strong mixed-mode I and II, and interacting cracks have been used as the case studies. A new technique has been proposed to identify the crack tip from thermoelastic images. It has also been shown that using three terms of Williams's stress field formulation to determine the Tstress, yields a more accurate solution than using only the first two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…Studies have also been done to examine the influence of crack closure and residual stress on the thermoelastic response of a crack. The effects are noticeable 25 and support conclusions that the SIF deduced from TSA is the effective value (DK eff ), 30 which reflects the actual rather than nominal driving force for crack growth. The distinction was illustrated in Diaz et al, 26 where SIF measurements furnished by TSA matched theoretical values only once the latter were corrected for the influence of closure and residual stress.…”
Section: Rajic and Stevesupporting
confidence: 72%
See 1 more Smart Citation
“…Studies have also been done to examine the influence of crack closure and residual stress on the thermoelastic response of a crack. The effects are noticeable 25 and support conclusions that the SIF deduced from TSA is the effective value (DK eff ), 30 which reflects the actual rather than nominal driving force for crack growth. The distinction was illustrated in Diaz et al, 26 where SIF measurements furnished by TSA matched theoretical values only once the latter were corrected for the influence of closure and residual stress.…”
Section: Rajic and Stevesupporting
confidence: 72%
“…For reference, the stress amplitude in the far-field of these scans is 25 MPa. It is worth noting that although thermoelastic scans of fatigue cracks have been reported previously, [24][25][26] this is the first example of a scan produced by a microbolometer. Setting aside factors relating to system optics (e.g.…”
Section: Structural Health Monitoringmentioning
confidence: 76%
“…al. [17] mentions that this effect is due to the stress term known as Tstress which is defined as the second non-singular term in Williams's crack tip stress field solution. Also refers to the Cotterell studies [18] where he says that the T-stress controls the stability of the crack direction as well as assumed that the ideal direction for crack growth is along the line of symmetry of the stress distribution ahead of the crack tip and concluded that if the sign of the T-stress is negative then the crack path has a tendency to return to its original ideal path (referred to as 'directionally stable').…”
Section: Discussionmentioning
confidence: 99%
“…One cannot predict the direction and path of crack propagation in rocks without crack initiation criterion (or fracture criterion), which is required to judge whether a crack implemented in many studies (Castro et al 2016;Gupta et al 2015;Kong et al 1995;Maiti and Smith 1983;Mróz and Mróz 2010;Smith et al 2001;Zanganeh et al 2008).…”
Section: Crack Extension Criteriamentioning
confidence: 99%